2015
DOI: 10.1002/nag.2395
|View full text |Cite
|
Sign up to set email alerts
|

A stability criterion for elasto‐viscoplastic constitutive relationships

Abstract: SUMMARYIn this paper, the onset of mechanical instability in time-sensitive elasto-viscoplastic solids is theoretically analyzed at the constitutive level and associated with the occurrence of 'spontaneous accelerations' under stationary external perturbations. For this purpose, a second-order form of Perzyna's constitutive equations is first derived by time differentiation, and a sufficient stability condition is identified for general mixed loading programs. These loading conditions are in fact the most gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…This fact not only makes extension to viscoplasticity less straightforward but also poses conceptual questions about the effects of convexity losses experienced by these functions in the overstress regime (ie, outside the f = 0/ g = 0 loci). Expected consequences might concern the predicted stability of the constitutive response, a subject so far never explored from this standpoint. When documented, convexity‐related issues might be remedied by resorting to recent convexification techniques …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact not only makes extension to viscoplasticity less straightforward but also poses conceptual questions about the effects of convexity losses experienced by these functions in the overstress regime (ie, outside the f = 0/ g = 0 loci). Expected consequences might concern the predicted stability of the constitutive response, a subject so far never explored from this standpoint. When documented, convexity‐related issues might be remedied by resorting to recent convexification techniques …”
Section: Discussionmentioning
confidence: 99%
“…Here, the former approach in the version proposed by Perzyna will be followed because of its proven capability to reproduce the rate dependence of both fine‐ and coarse‐grained soils, including creep and relaxation phenomena. Importantly, Perzyna viscoplasticity has also proven a suitable conceptual platform for the interpretation of several soil instabilities …”
Section: Introductionmentioning
confidence: 99%
“…() Some authors have explained the temporal evolution of the failure process by remarking the role of the instability line during the initiation of an accelerating response. () This concept has been recently incorporated by Pisanò and di Prisco within a rigorous theoretical framework able to interpret unstable phenomena in viscous solids. The performance of this theory has been explored with reference to the undrained creep of loose sands by Marinelli et al, who showed that these particular class of instability criteria is able to detect the accelerating trends of behavior characterizing delayed liquefaction.…”
Section: Delayed Liquefaction For Quasi‐saturated Soilsmentioning
confidence: 99%
“…The performance of this theory has been explored with reference to the undrained creep of loose sands by Marinelli et al, who showed that these particular class of instability criteria is able to detect the accelerating trends of behavior characterizing delayed liquefaction. Here, the theory proposed by Pisanò and di Prisco is specialized to quasi‐saturated soils by incorporating the role of occluded gas bubbles. For this purpose, the viscoplastic response is rearranged by means of a new constitutive operator relating accelerations and rates of the response variables.…”
Section: Delayed Liquefaction For Quasi‐saturated Soilsmentioning
confidence: 99%
See 1 more Smart Citation